2014
DOI: 10.1111/napa.12048
|View full text |Cite
|
Sign up to set email alerts
|

Georeferencing a Cold Case Victim With Lead, Strontium, Carbon, and Oxygen Isotopes

Abstract: Two men walking across a bridge along highway I-75 found a young woman's body floating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…As discussed in the introduction section, in all of the published four multi‐isotope case studies , the authors suggested a nonlocal origin for the victims. Based on these works, we can rule out “local” origin of human remains if the isotopic signal in the decedent is distinct from the expected isotopic range for the local population.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…As discussed in the introduction section, in all of the published four multi‐isotope case studies , the authors suggested a nonlocal origin for the victims. Based on these works, we can rule out “local” origin of human remains if the isotopic signal in the decedent is distinct from the expected isotopic range for the local population.…”
Section: Discussionmentioning
confidence: 95%
“…Carbon (C), oxygen (O), strontium (Sr), and lead (Pb) isotopic data obtained from human skeletal remains can be used as a tool for reconstructing human origins, migration, and diet in prehistoric and historic populations . Similarly, multi‐isotopic analysis of contemporary humans can provide information about the birthplace, geographical mobility, and diet of unidentified human remains . In four recent contemporary case studies , the multi‐isotope data showed that the victims were foreigners to the region where the remains were found.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have observed relationships between the 87 Sr/ 86 Sr ratio of hair and possible exogenous sources of Sr in the environment (e.g., 5,11,47,50,51,54,63 ). Recently, a significant relationship between the 87 Sr/ 86 Sr ratios of hair and tap water was observed within a single city that had municipal water with several distinct ratios.…”
Section: Relationships Between the Sr-isotope Ratios Of Hair And Tamentioning
confidence: 99%